Exploring the influence of student leadership on self-resilience for national secondary school students in Malaysia - Noorhazlina Fairuz Fauzi; Yahya Don; Mat Rahimi Yusof (International Journal of Evaluation and Research in Education (IJERE), 2023)
Students are the backbone to future leadership and the catalyst for the success of a country. Hence, student leadership with high self-resilience should be shaped and built as early as possible. Student leaders with low self-resilience will portray negative feelings and not able to play a full role. To identify student leadership practices and their relationship with national secondary school students’ resilience in the eastern zone states of Malaysia, this quantitative survey study used questionnaires adapted from the inventory of student leadership practices (S-LPI) to measure the dimensions of student leadership on 394 students selected through cluster random sampling while a self-resilience questionnaire was used to measure students’ level of self-resilience. Using the statistical package for social science (SPSS) version 26 for descriptive data and partial least squares structural equation modelling (PLS-SEM 3) for inferential statistics, the results showed that the dimensions of inspire a shared vision, challenge a processes and enable to act were dimensions of student leadership practices that had significantly affected self-resilience while student leadership practices with flexible, orderly self-resilience and prioritizing social relationships in organizations were factors for shaping future leaders.